Desarrollo de pasantía en la empresa Ortopédicos Futuro Colombia SAS (2023)
This document describes the application and reinforces the theoretical knowledge earned during these semesters in the International Trade degree to the practice through a business internship program in Ortopédicos Futuro SAS company. The internship was made in the Purchasing department supporting national and international duties in all lines of business of the company. Due to the implementation of activities and deep analysis in the area through a DOFA, the implementation of improvement processes in the area of international purchase was sought and a matrix was established for the measurement of indicators of foreign trade operations of the company from which results were obtained from these and allowed decision making in real-time. Keywords: Customs agency, Storage, Advance payment, Foreign trade, Commercial invoice, International freight, Lift, Import, Incoterms, Indicators, Nationalization, Orthopedics, Foreign Purchase Order, Country of origin, Internship, Proforma, Suppliers, Customs duties